Enzymes for the biochemical route of second-generation ethanol: Production by solid-state cultivation as a feasible and sustainable alternative - Casciatori, Fernanda Perpétua; Casciatori-Frassatto, Priscila Aparecida [UNESP] (My University, 2018)
Considering the main four steps for second-generation ethanol (E2G) production from a vegetal biomass, namely (1) pretreatment, (2) hydrolysis, (3) fermentation and (4) distillation, hydrolysis may be considered one of the most challenging operations. Although chemical or acidic hydrolysis is possible and somehow efficient, the enzymatic route of vegetal biomasses saccharification is prefered in most of the applications because it presents some advantages like mild conditions of operation, high specificity of the enymes and low generation of toxic residues, either for the environment or for the sucessive steps of the E2G production. However, mainly due to the restricted worldwide marketshare of enzymes, the cost of hydrolytic enzymes (such as cellulases, hemicellulases, ligninases and amylases) and of auxilar enzymes associated can make the enzymatic route of hydrolysis of vegetal biomasses unfeasible. In this context, the solidstate cultivation (SSC), especially of filamentous fungi on agro-industrial by-products (such as bagasses, brans, fruit pulp and peels and remaining on crops leaves) appears as a feasible and sustainable alternative for the supply of enzymes for E2G production chain. The main idea defended here is that the enzymes can be produced within the same biorefinery that have E2G as the major product, in which a paralel line can, at one end, be supplied with highly available vegetal biomasses as substrates for microbial cultivation and enzymes synthesis and, at the opposite end, supply the needed enzymes cocktails as an input for enzymatic hydrolysis or saccharification step on the central line of the biorefinery, the E2G production chain. On the above, in the current chapter, an overview of several works on enzymes production (cellulases, hemicellulases and amylases) by SSC using different types of bioreactors (packed-beds and rotating drums) is presented and discussed on the light of the available literature and on the findings of the research group with which the author has contributed since last decade.
Keywords: Agro-industrial by-products; Enzymatic hydrolysis; Second-generation ethanol; Solid-state cultivation